Paired bulk organic and individual amino acid δ15N analyses of bivalve shell periostracum: A paleoceanographic proxy for water source variability and nitrogen cycling processes. (1st June 2019) - Whitney, Nina M.; Johnson, Beverly J.; Dostie, Philip T.; Luzier, Katherine; Wanamaker, Alan D.
Abstract: Developing high-resolution, well-dated, marine proxies of environmental, climatic, and oceanographic conditions is critical in order to advance our understanding of the ocean's role in the global climate system. While some work has investigated bulk and compound specific stable nitrogen isotope (δ 15 N) values in bivalve shells as proxies for environmental variability, the small concentrations of nitrogen found in the organic matrix of the shell calcium carbonate (hereafter carbonate) makes developing high resolution records challenging. This study investigates the potential of using the bulk and amino acid δ 15 N values of bivalve periostracum, the protein layer on the outside of the shell, as a proxy archive of nitrogen cycling processes and water source variability. Bulk δ 15 N values were measured on the periostracum, carbonate, and adductor muscle of Arctica islandica shells collected in the Gulf of Maine. Increased variability of isotopic values across growth lines compared to along growth lines support mechanistic reasoning based on growth processes that periostracum is recording changes in δ 15 N values over the course of the clam's lifetime (up to 500 years). In addition, the statistically significant relationship between periostracum δ 15 N values and contemporaneous carbonate δ 15 N values of the same shell (r = 0.82, p < 0.0001, n = 40) suggests that periostracum preserves a similar δ 15 N signal to that preserved in the carbonate. This finding, coupled with the fact that source amino acid δ 15 N values of periostracum are similar to that of the adductor muscle and the particulate organic matter (POM) consumed by the clam, suggests that periostracum bulk δ 15 N values reflect the δ 15 N values of the clam's food source. The isotopic offsets between periostracum, carbonate, and adductor muscle δ 15 N values are primarily caused by differences in amino acid composition of the different tissue types, as evidenced by isotope mass balance calculations, although may also be related to differences in δ 15 N values of the individual amino acids of the different tissue types, especially for the trophic amino acids. Compound specific δ 15 N analyses of the periostracum of A. islandica shells were used to determine that the calculated trophic position of the clams in this study (1.4 ± 0.4) did not change significantly between 1783 and 1997. Phenylalanine δ 15 N values over the last 70 years show similar trends to that of the bulk record, suggesting that changes in bulk δ 15 N values over that time period are related to changes in baseline δ 15 N values. Periostracum δ 15 N values from shells collected in the western Gulf of Maine have decreased by ∼1‰ since the mid-1920s. This trend (−0.008‰/year) is not statistically different from the trend of previously published δ 15 N values of deep-sea corals from the entrance to the Gulf of Maine over the same time period. This coral record has been shown to indicate a shift in water source in the region and therefore the similarity between the two records suggest that changes in periostracum δ 15 N values are reflecting broader North Atlantic hydrographic changes. Our study introduces a new, high-resolution, and absolutely dated paleoceanographic proxy of baseline δ 15 N values, presenting the opportunity for future reconstructions of aspects of nitrogen cycling and water source changes in the global oceans.